Introducing change management education program for family medicine residents: a demonstration project - Singh, Jitendra; Singer, Alexander; Paige, Allison (Canadian Medical Education Journal, 2023)
Implication Statement The project presents an innovative mixed learning approach program to provide basic change management training for family medicine residents. Developed by a team of faculty experts in the Department of Family Medicine at the University of Manitoba, this three-to-four-hour training program provided residents an understanding of an approach to change management that systematically plans, implements, and evaluates new initiatives in healthcare settings. Students reported that change management is important for their success as healthcare professionals. This program could easily be replicated.